The stresses and coping reactions of separated women an exploratory study - Relucio, Edelvina S. (Philippine Journal of Psychology, 1995)
The study explored the different stresses and coping reactions of separated women as well as the different phases of marital separation by using the multiple case study method. The in-depth interview was used as the main instrument in the study of seven separated women. Data analysis was done by searching for emerging patterns. Among those found were common patterns in the characteristics of the women and their ex-spouses; the stresses experienced by the women; coping reactions before and after the separation; the characteristics of the marriage itself; and the reasons for their initial efforts to keep the marriage intact. Infidelity was found to be a common problem. Marital separation was found to be a process with several phases. Patterns in the dynamics of the women were discussed, particularly the pattern of emotional abuse as well as the influence of culture and religion. The importance of time and the family of origin contribute to the continuous but slow process of growth and healing.